2019
DOI: 10.7150/thno.32376
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic features from PSMA PET for non-invasive intraprostatic tumor discrimination and characterization in patients with intermediate- and high-risk prostate cancer - a comparison study with histology reference

Abstract: Purpose: To evaluate the performance of radiomic features (RF) derived from PSMA PET for intraprostatic tumor discrimination and non-invasive characterization of Gleason score (GS) and pelvic lymph node status. Patients and methods: Patients with prostate cancer (PCa) who underwent [ 68 Ga]-PSMA-11 PET/CT followed by radical prostatectomy and pelvic lymph node dissection were prospectively enrolled (n=20). Coregistered histopathological gross tumor volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
115
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
2

Relationship

4
6

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 57 publications
4
115
1
2
Order By: Relevance
“…Multiparametric magnetic resonance imaging (mpMRI) is the current gold standard for PCa detection [4] but has been shown to miss pivotal tumor lesions and underestimates their volume [6,7]. Instead prostate-specific membrane antigen positron emission tomography (PSMA-PET) is emerging as a promising technique to improve tumor lesion detection [8][9][10][11][12][13][14][15], focal therapy guidance [16], and non-invasive PCa characterization [17].…”
Section: Introductionmentioning
confidence: 99%
“…Multiparametric magnetic resonance imaging (mpMRI) is the current gold standard for PCa detection [4] but has been shown to miss pivotal tumor lesions and underestimates their volume [6,7]. Instead prostate-specific membrane antigen positron emission tomography (PSMA-PET) is emerging as a promising technique to improve tumor lesion detection [8][9][10][11][12][13][14][15], focal therapy guidance [16], and non-invasive PCa characterization [17].…”
Section: Introductionmentioning
confidence: 99%
“…All these studies concluded that PSMA-PET provides superior detection of intraprostatic tumour lesions with better sensitivity than mpMRI. Thus, PSMA-PET/CT can be used to enhance mpMRI to provide improved detection and even characterization [41] of lesions.…”
Section: Discussionmentioning
confidence: 99%
“…All these studies concluded that PSMA-PET provides superior detection of intraprostatic tumour lesions with better sensitivity than mpMRI. 330 Thus, PSMA-PET/CT can be used to enhance mpMRI to provide improved detection and even characterization [33] of lesions.…”
Section: Discussionmentioning
confidence: 99%